A produção de pequenos objetos de madeira: um estudo de caso: a empresa "Móveis Souza" - MONTEIRO, Shirley do Socorro Magalhães (2006)
This research was organized around the production of a small wooden object, so as to try to depict its biography, from a point of observation at enterprise Móveis Souza, where it is conceived and made. In achieving the production of this object cooperate the owner and his son, as well as the wife of the former who manages the family business. Object creation, which means art to the owner, as well as the specific work organizatioen constitute unique conditions which are essential to achieve the production of such object. Moreover, the circumstances in which the owner starts using wood residues, and how this decision attaches environmental quality to production, which on its turn is the central elements connected to the invention of a regional production. The introduction of design in the state of Pará mediates the invention of Pará and Amazonian regional products.